Sinophile Consumption: Chinese Restaurants and Consumer Culture in Turn-of-the-Century American Cities. Issue 3 (2nd September 2019) - King, Samuel C.
ABSTRACT: The "chop suey craze, " the moment at the turn of the twentieth century when Chinese restaurants enjoyed unprecedented mainstream popularity in the United States, has received much attention in the literature on the American history of Chinese food. Much of this scholarship has attributed the craze primarily to the advent in the late nineteenth century of chop suey, and to the 1896 visit of Li Hongzhang to New York, while other works have emphasized new consumption imperatives stemming from the shift to a culture of empire at the turn of the century. This article seeks to intervene in this literature by shifting analytical focus away from these explanations and instead argue that the chop suey craze formed part of a larger resurgence in periodic American enthusiasm for China and Chinese cultural products, which I term Sinophilia, engendered by the emergence of an American empire in the Pacific in the 1890s.